1992
DOI: 10.1055/s-2007-1024611
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Metabolism, Muscular Fatigue and Muscle Wasting

Abstract: Recent investigations from our and other laboratories indicate that glycogen is a carbon-chain precursor in muscle for the synthesis of TCA cycle intermediates and glutamine. During intense exercise and in conditions of a relative lack of energy (hypoxia, trauma, sepsis) the metabolism of branched-chain amino acids (BCAA) is accelerated in muscle. In the primary BCAA aminotransferase reaction 2-oxoglutarate is used as amino-group acceptor (putting a carbon-drain on the TCA cycle) under formation of glutamate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 5 publications
(9 reference statements)
1
24
0
1
Order By: Relevance
“…Hypoxia is associated with an increased production of free radicals (Simon-Schnass 1994; Vasankari et al 1997) and thus the production of e ective free radical scavengers would prove bene®cial. Finally, Wagenmakers (1992) suggested that the hyperadrenalinaemia associated with chronic hypoxia would result in a depletion of 2-oxoglutarate which is required for activation of the branched-chain amino acid aminotransferase reaction that ultimately produces glutamine, and hyperadrenalinaemia decreases the rate of glutamine transport out of rat muscle incubated in vitro (Garber et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is associated with an increased production of free radicals (Simon-Schnass 1994; Vasankari et al 1997) and thus the production of e ective free radical scavengers would prove bene®cial. Finally, Wagenmakers (1992) suggested that the hyperadrenalinaemia associated with chronic hypoxia would result in a depletion of 2-oxoglutarate which is required for activation of the branched-chain amino acid aminotransferase reaction that ultimately produces glutamine, and hyperadrenalinaemia decreases the rate of glutamine transport out of rat muscle incubated in vitro (Garber et al 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Although oral glutamine supplementation halved bacterial translocation to mesenteric lymph nodes (a measure of enterocyte barrier dysfunction) in starved rats exposed to a simulated altitude of 7,000 m for 72 h [ 31 ], the dose was 0.5/100 g body weight, equivalent to 350 g glutamine/day for a 70 kg human exposed to these artifi cial conditions. Despite speculation that glutamine supplementation might have benefi cial effects on muscle function [ 32 ], we have seen that glutamine synthetase actually increases on short-term exposure to high altitude [ 30 ] and there is no objective evidence that glutamine supplementation enhances or protects small intestinal function in normal individuals at high altitude.…”
Section: Effect Of Hypoxia On Protein Absorption Normal Protein Digesmentioning
confidence: 98%
“…Depending on the intensity and/or duration of exercise, muscle [NH3] may be high enough to quickly diffuse from the muscle tissue to the blood, however, the mechanism underlying the regulation of AMP deamination in human skeletal muscle remains unclear (9). Because NH3 production reflects the extent of the reliance of active muscle on amino acid catabolism together with the inability to match ATP supply with demand (16), and also the adaptation of muscle fibres to the shifts in energy status, exercise-induced hyperammonemia has been associated with the development of fatigue (1,20).…”
mentioning
confidence: 99%